The unraveled truffle secrets - Zampieri, Elisa; Mello, Antonietta (Mushroom Research, 2012)
Truffles, ectomycorrhizal hypogeous fungi living in symbiosis with tree roots, show differences in their organoleptic properties and their geographical distribution. The ecology and the genomics of some truffles were deeply studied in the last years, thanks to the development of species-specific primers, the Tuber melanosporum genome sequencing and the advances in the technologies. Numerous Tuber secrets have been unraveled, but many steps are still required in order to have a complete understanding of the Tuber life cycle, i. e., ascocarp formation.